(untitled) (Journal of Parents and Teachers, 2018)
Art education is changing the learning situation in school. New artistic methodologies conceive an educational curriculum that is framed in the creative processes that allow active and meaningful learning. The multidisciplinary of art helps teachers to develop methodologies that favor interaction, manipulation, experimentation and interiorization of curricular contents from the game and the resolution of problems. Connect knowledge, relate and value, is critical of the environment, makes proposals for social transformation.